Job satisfaction on talent management and turnover intention among private secondary schools - Nimtur, Bethel Manna; Kusa, Nanfa Danjuma; Olanrewaju, David Sunday (Goodwood Publishing, 2023)
Purpose: This study investigates the role of job satisfaction in the relationship between talent management dimensions and turnover intention among private secondary school teachers in Langtang North LGA in the plateau state. Research Methodology: The study used a survey to collect data from a population of 628 teachers. The sample size of 244 was determined using the Taro Yamane formula. The data were collected using questionnaires. Data were analyzed using multiple regression with the aid of partial least squares structural equation Modelling (PLS-SEM) using SmartPLS 3.0 to evaluate the hypothesized relationships. Results: The results reveal a significant relationship between talent attraction and turnover intention. Second, there is no relationship between talent development and turnover intention, a negative relationship between talent retention and turnover intention, and a positive relationship between talent attraction and job satisfaction. Talent development and retention both had a negative relationship with job satisfaction, and job satisfaction did not moderate the relationship between talent management dimensions and turnover intention. Limitations: The study was limited to 244 teachers in the Langtang North Local Government Area. This limited the involvement of other categories of teachers in the study. Contribution: This study provides valuable insights to policymakers in the educational sector to create a holistic attraction and selection policy that will ensure that teachers with higher retention potentials are employed to reduce the cost associated with teachers’ turnover and to understand the factors that cause employee turnover and implement effective policies and regulations that can enhance the retention of teachers.